Estudo de biopolímeros para modificação da porosidade durante a sinterização da hidroxiapatita - Macêdo, Ana Angélica Mathias (2010)
This work reports the study of polymers for modification of porosity during sintering of hydroxyapatite. The material used was hydroxyapatite and the biopolymers: galactomannan, xanthan and chitosan. Bioceramics were obtained from the mixture of hydroxyapatite (HAP) and galactomannan (Gal), galactomannan / chitosan (GalQ) and galactomannan / xanthan (Galaxy) in concentrations of 10, 20 and 30% of biopolymers. The results obtained by X-ray diffraction indicated that the method of synthesis and sintering were sufficient to show in the formation of only one phase of the HAP and to the amorphous phase for the Gal, GalQ and GalX. Infrared spectroscopy showed typical bands of HAP, Gal, GalQ and GalX, confirming the presence of Chitosan and Xanthan interacting with Gal. The viscosity showed shear thinning behavior in the GAL, as well as the blends GalQ and galaxies, and that Galaxy had a higher viscosity. The theiTnal behavior showed that Gal, GalQ and GalX have thermal stability around 300 ° C. The dielectric permittivity showed that the addition ofXanthan and Chitosan favored the increase of dielectric constant, confirming the synergy between the biopolymers. The hardness of bioceramics Gal, GalQ and GalX (30, 20 and 10) showed that the bioceramics composed only of galactomaiman, showed a higher hardness when compared to bioceramics (GalQ and GalX), moreover, the bioceramics composed of a higher concentration of HAP showed a higher hardness. The density of the bioceramics was also higher for the bioceramic containing only galactomannan, except for Gal30. Similarly, the results obtained with the hardness, the bioceramics composed with the greatest amount of hydroxyapatite showed higher densities. In micrographs (SEM) of bioceramics Gal (30, 20 and 10), 25000 X, what with the heat treatment, the grain size increased, eliminating most of the porosity, thus consolidating the samples. The bioceramic with higher polymers are those with dielectric constant (s) lower, with the addition of xanthan to Gal favored the increase da e' on the bioceramic. These results suggest the possibility of the developing bioceramics with HAP and Gal, GalQ and GalX to be useful in implants.